Density fluctuation correlation measurements in ASDEX Upgrade using poloidal and radial correlation reflectometry. (8th May 2018) - Prisiazhniuk, D; Conway, G D; Krämer-Flecken, A; Stroth, U
Abstract: The poloidal correlation reflectometry diagnostic operated in ordinary mode with additional radial correlation channel is applied in this paper to investigate the correlation of the turbulent density fluctuations. The perpendicular and radial correlation lengths, l ⊥ and l r, the perpendicular velocity v⊥ and the dissipation (mutation) time τ d are measured simultaneously from the outer core to edge in the L-mode plasmas of ASDEX Upgrade. It is shown that in the outer core region (0.6 <  ρ pol  < 0.9) the measured correlation lengths scale with the drift wave length, l ⊥  ≈ 5 ρ s and l r  ≈ 10 ρ s, while the dissipation time is inversely correlated with the velocity τ d  ≈ 40/ v ⊥ ( τ d is in μ s and v ⊥ in km s –1 ). In the pedestal region (0.925 <  ρ pol  < 0.98), where the E  ×  B shear flows are present, a loss of measured correlation is observed which can be explained by a combination of small propagation velocity and an additional reduction of τ d . In the E r well region ( ρ pol  ≈ 0.99), the measured perpendicular correlation length increases l ⊥ ≈ 13 ρ s and the radial correlation length decreases l r  ≈ 4 ρ s compared to the outer core values. The correlation measurements are interpreted in the frame of the linear regime of reflectometry (applied only to ρ pol  < 0.9). Using the Born approximation we show that the finite wavenumber sensitivity of the reflectometer increases the measured l ⊥ and l r, but does not affect the measured τ d . By the including diagnostic correction the real correlation lengths l ⊥  ≈  l r  ≈ 3 ρ s are estimated.